ANALISIS STRATEGI KEUNGGULAN BERSAING DALAM RANGKA MENINGKATKAN VOLUME PENJULAN PADA BISNIS OPTIK(STUDI KASUS PADA BISNIS OPTIK DI PEKANBARU) - Maya Sari; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research conducted on optical business in Pekanbaru, this study aims to identify and analyze the implementation of the strategy of competitive advantage in order to increase the volume of sales in the optical business in Pekanbaru.Methods of data collection using questionnaires. The questionnaire is the technique of data collection is done by providing a set of written questions to the respondent’s in charge. The sample is part of the number and characteristics of the population is owned by as many as 36 business owners optical. Data obtained from the questioner and then processed to then tested with statistics through SPSS program. the results showed that competitive advantage strategy cost leadership strategy (x1) and the differentiation strategy (x2) has positive influence on the sales volume. The calculated result is known that R square is coefficient of determination. So that, it obtained the value of R square is about 0,725. It is meaned that the influence of variable cost leadership and differentiation variable was 72,5% to sales volume.Keywords: competitive strategy,cost leadership, differentiation, sales volume.